Teacher’s Attitudes on Ambient Teaching Implementation in the Beginning of Environmental Education - Bajić, Milica; Kozoderovic, Gordana; Maric, Mia (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
In everyday practice, teachers are faced with the choice of appropriate and adaptable models of environmental learning and the possibilities for their realization in practice. Ambient Teaching (AT) provides a flexible approach to the implementation of comprehensive environmental education. The research in this paper was aimed at examining the structure of teachers' attitudes on the application of ambient teaching in initial ecological education. Tasks of the research are focused on the analysis of attitudes on the application of ambient teaching, attitudes on the efficiency of its application to environmental education, as well as attitudes on the efficiency of its implementation by involving schools in eco-projects. The socio-demographic questionnaire and questionnaire for measuring attitudes were applied as the instruments of methodology. The sample consisted of 80 teachers from three primary schools from the territory of the Novi Sad municipality. The obtained results indicate that teachers have a positive attitude to the implementation of ecological content through ambient teaching. However, in order to more frequently apply this way of teaching, it is necessary for the schools to take part in a specific ecological project and achieve better quality education for both teachers and students.
Keywords: Ambient Teaching; environmental education; teachers; ecological projects